Theologies and Ethics of Justice: New Directions for Islamic Thought in the 21st Century (American Journal of Islam and Society, 2017)
The Summer Institute for Scholars 2017, held at the IIIT headquarters inHerndon, VA, from July 26-29, brought together a group of scholars to address“Theologies and Ethics of Justice: New Directions for Islamic Thoughtin the 21st Century.” To present as many of their ideas as possible, the widerangingand thought-provoking comments of the chairs and discussants arenot recountedThe event began with welcoming remarks by Ermin Sinanović (programdirector and director of research, IIIT), Abubaker al-Shingieti (executive director,IIIT) and Hisham Altalib (president, IIIT). The participating scholars,students, and special guests were introduced and viewed a film on IIIT.The special panel on “Justice in Islamic Thought” was addressed byRamon Harvey (Ebrahim College, London) and Jonathan A.C. Brown(Georgetown University; via Skype). Ramon Harvey’s paper, “The Qur’anand the Just Society: An Enquiry into Scriptural Theology, Ethics, andHermeneutics,” introduced the theoretical framework of his forthcomingbook, The Qur’an and the Just Society. He presented the basic underlyingenquiry: the search for the meaning of societal justice within the Qur’anicworldview. His argument proceeded in three steps: (1) justice in the Qur’anmust be situated within the broader “moral narrative” about the spiritualjourney of souls and societies and from which an implicit moral theologycan be detected; (2) that it is possible to build on such Qur’anic indicationsto articulate a theological and ethical system that models it; and (3) that sucha system gives a meaningful epistemological foundation for a hermeneuticsto discover the Qur’an’s basic principles of justice when contextualizedwithin the initial Muslim community led by Prophet Muhammad ...